Cross-continental analysis of coastal biodiversity change. (21st December 2020) - Rishworth, Gavin M.; Adams, Janine B.; Bird, Matthew S.; Carrasco, Nicola K.; Dänhardt, Andreas; Dannheim, Jennifer; Lemley, Daniel A.; Pistorius, Pierre A.; Scheiffarth, Gregor; Hillebrand, Helmut
Abstract : Whereas the anthropogenic impact on marine biodiversity is undebated, the quantification and prediction of this change are not trivial. Simple traditional measures of biodiversity (e.g. richness, diversity indices) do not capture the magnitude and direction of changes in species or functional composition. In this paper, we apply recently developed methods for measuring biodiversity turnover to time-series data of four broad taxonomic groups from two coastal regions: the southern North Sea (Germany) and the South African coast. Both areas share geomorphological features and ecosystem types, allowing for a critical assessment of the most informative metrics of biodiversity change across organism groups. We found little evidence for directional trends in univariate metrics of diversity for either the effective number of taxa or the amount of richness change. However, turnover in composition was high (on average nearly 30% of identities when addressing presence or absence of species) and even higher when taking the relative dominance of species into account. This turnover accumulated over time at similar rates across regions and organism groups. We conclude that biodiversity metrics responsive to turnover provide a more accurate reflection of community change relative to conventional metrics (absolute richness or relative abundance) and are spatially broadly applicable. This article is part of the theme issue 'Integrative research perspectives on marine conservation'.